2023
DOI: 10.1055/a-2015-1080
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Juvenile Xanthogranuloma with a Novel MYH9-FLT3 Fusion Presenting as a Blueberry Muffin Rash in a Neonate

Abstract: INTRODUCTION: Juvenile Xanthogranuloma (JXG) is a benign proliferative histiocytic disorder of the dendritic cell phenotype. It mostly presents in the pediatric age group as a solitary skin lesion. We describe a rare case of an infant born with disseminated JXG who presented with a blueberry muffin rash at birth. CASE DESCRIPTION: A term infant was noted to have multiple petechiae, purple nodules, and macules (1 mm-2 cm in diameter) and hepatosplenomegaly, at the time of birth. Further investigations revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“… 31 It is the only myosin class II protein that is highly expressed in T cells and has been linked to T-cell motility, 32 as well as immunological synapses and T-cell activation. 33 Fusions involving MYH9 have been found in other disorders and include MYH9::FLT3 , 34 MYH9::ROS1 , 35 and MYH9::USP6 . 36 Similarly, PDGFRB fusion proteins have been described in myeloid disorders and myeloid leukemia 15 , 20 , 37 , 38 and, indeed, aberrant expression of this receptor tyrosine kinase has been described in several cancer entities.…”
Section: Discussionmentioning
confidence: 99%
“… 31 It is the only myosin class II protein that is highly expressed in T cells and has been linked to T-cell motility, 32 as well as immunological synapses and T-cell activation. 33 Fusions involving MYH9 have been found in other disorders and include MYH9::FLT3 , 34 MYH9::ROS1 , 35 and MYH9::USP6 . 36 Similarly, PDGFRB fusion proteins have been described in myeloid disorders and myeloid leukemia 15 , 20 , 37 , 38 and, indeed, aberrant expression of this receptor tyrosine kinase has been described in several cancer entities.…”
Section: Discussionmentioning
confidence: 99%
“…In this heterogeneous group of diseases, some of the findings on brain imaging have been seen in other children with the same disease without cholestasis 94–97 . However, for erythrophagocytic lymphohistiocytosis, juvenile xanthogranuloma, unknown cholestatic liver disease and kernicterus scanned at diagnosis and one case of Kabuki scanned at 6–11 years of not all findings have previously been described in children without cholestasis 98–102 . The findings can be seen in Table 2A and Table S6.…”
Section: Resultsmentioning
confidence: 89%
“…[94][95][96][97] However, for erythrophagocytic lymphohistiocytosis, juvenile xanthogranuloma, unknown cholestatic liver disease and kernicterus scanned at diagnosis and one case of Kabuki scanned at 6-11 years of not all findings have previously been described in children without cholestasis. [98][99][100][101][102] The findings can be seen in Table 2A and Table S6.…”
Section: Number Of Participants Primary Diagnoses: Number Of Studies ...mentioning
confidence: 79%
“…Interestingly, upregulation of ALK phosphorylation promoted the phosphorylation of PI3K/AKT, STAT3, and MEK/ERK, indicating that ALK induces cellular hyperplasia through various signaling pathways 5 . Additional studies have identified MRC1‐PDGFRB, RNF11‐BRAF , and MYH9‐FLT3 fusion proteins in SJXG 5,19 …”
Section: Genetic Aberrations In the Pathogenesis Of Sjxgmentioning
confidence: 99%
“…5 Additional studies have identified MRC1-PDGFRB, RNF11-BRAF, and MYH9-FLT3 fusion proteins in SJXG. 5,19 As recurrent BRAFV600E mutations and ALK translocations have been detected in histiocytosis, we collected 23 cases of SJXG to screen for two common types of genetic abnormalities in a recent study, and the results showed that 34.7% (8/23) of these cases harbored ALK translocations and 17.4% (4/23) carried BRAFV600E mutants. 12 Our study indicates that ALK translocations play an important role in the pathogenesis of SJXG, which is different from BRAFV600E mutations in LCH and ECD.…”
mentioning
confidence: 99%